Direct pulp capping with novel nanostructural materials based on calcium silicate systems and hydroxyapatite - Popović-Bajić Marijana; Petrović Violeta; Opačić-Galić Vanja; Danilović Vesna; Jokanović Vukoman; Prokić Branislav; Bolka-Prokić Bogomir; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2016)
Introduction Direct pulp capping is an important therapeutic method that has goal to provide formation of dentin bridge and healing process of the pulp. The aim of this study was to investigate the effects of new nanostructural materials based on calcium silicate systems and hydroxyapatite on exposed dental pulp in Vietnamese pigs. Material and Methods The study was conducted on 30 teeth of two Vietnamese pigs (Sus scrofa verus). On buccal surfaces of incisors, canines and first premolars, class V cavities were prepared with a small round bur and pulp horn was exposed. In the first experimental group (10 teeth) the perforation was covered with new nanostructural material based on calcium silicate systems (CS). In the second experimental group, the perforation was covered with compound of calcium silicate systems and hydroxyapatite (HA-CS) (10 teeth). In the control group, exposed pulp was covered with Pro Root MTA® (Dentsply Tulsa Dental, Johnson City, TN, USA) (10 teeth). All cavities were restored with glass ionomer cement (GC Fuji VIII, GC Corporation, Tokyo, Japan). Observation period was 28 days. After sacrificing the animals, histological preparations were done to analyze the presence of dentin bridge, inflammatory reaction of the pulp, pulp tissue reorganization and the presence of bacteria. Results Dentin bridge was observed in all teeth (experimental and control groups). Inflammation of the pulp was mild to moderate in all groups. Neoangiogenesis and many odontoblast like cells responsible for dentin bridge formation were detected. Necrosis was not observed in any case, neither the presence of Gram-positive bacteria in the pulp. Conclusion Histological analysis indicated favorable therapeutic effects of new nanostructural materials based on calcium silicate systems and hydroxyapatite for direct pulp capping in teeth of Vietnamese pigs.